1956
DOI: 10.1172/jci103266
|View full text |Cite
|
Sign up to set email alerts
|

Virilizing Adrenal Hyperplasia; A Genetic and Hormonal Study 1

Abstract: It is not at all unusual to find other affected children among the brothers and sisters of patients with virilizing adrenal hyperplasia. Such familial aggregations of affected children suggest, at least, a genetic basis for the condition at hand, and when the affected individuals are distributed in one generation only, there is a possibility that the condition is due to a mutant gene which finds obvious expression in the homozygote. This mode of inheritance for a possible gene responsible for virilizing adrena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
1
1

Year Published

1959
1959
1986
1986

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(40 citation statements)
references
References 18 publications
0
38
1
1
Order By: Relevance
“…From our investigation a frequency of CAH with and without salt loss in the Emilia-Romagna Re gion of 1/5,556 can be calculated. This corre sponds to a heterozygote frequency of 1/37, CAH being transmitted as an autosomal re cessive trait [14,15], The 4 cases we detected (3 females and 1 male) include two forms with salt loss (table I, cases 1 and 4), one form without salt loss (table I, case 2) and 1 case (table I. case 3) that might be described ery 5.556 children born. This corresponds to one heterozygote every' 300 subjects, for as a late [16,17] or acquired [18] or cryptic form [ 19] of CAH based on the high values of 17-OH-P and the absolute absence of clinical signs.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…From our investigation a frequency of CAH with and without salt loss in the Emilia-Romagna Re gion of 1/5,556 can be calculated. This corre sponds to a heterozygote frequency of 1/37, CAH being transmitted as an autosomal re cessive trait [14,15], The 4 cases we detected (3 females and 1 male) include two forms with salt loss (table I, cases 1 and 4), one form without salt loss (table I, case 2) and 1 case (table I. case 3) that might be described ery 5.556 children born. This corresponds to one heterozygote every' 300 subjects, for as a late [16,17] or acquired [18] or cryptic form [ 19] of CAH based on the high values of 17-OH-P and the absolute absence of clinical signs.…”
Section: Discussionmentioning
confidence: 63%
“…The reported incidence of CAH varies inter nationally from 1:490 in the Eskimos of Al aska to 1:67,000 in one of the American States [9][10][11][12][13][14]. The lack of a screening proce dure makes an estimation of the incidence questionable.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it appears clear that the two syndromes are genetically -distinct from each other ( 17) although there are reports which tend to question this conclusion (18). It has been suggested that the difference between the two syndromes is one of degree of block in 21-hydroxylation, the sodium-losing variety representing the more severe block (2,8).…”
Section: Methodsmentioning
confidence: 99%
“…The classical form of congenital adrenal hyperplasia with steroid 21-hydroxylase deficiency is transmitted by an autosomal recessive gene [1] and is closely linked to the HLA-B locus on the short arm of chromosome 6 [2] with peak total lod scores as high as 9.5 [3] and 15.65 [4] for 0 (recombinant fraction) = 0. Linkage disequilibrium with the HLA-Bw47;DR7 haplotype segment has been demonstrated [5][6][7], and more recently the gene has been further localized to the C4 region of the HLA supergene by molecular genetic techniques [8,9].…”
Section: Introductionmentioning
confidence: 99%